Initiatives to enhance the quality and efficiency of statin and PPI prescribing in the UK: impact and implications. (February 2010) - McGinn, Diane; Godman, Brian; Lonsdale, Julie; Way, Rosalind; Wettermark, Bjöörn; Haycox, Alan
Aim: To assess the impact of a range of national and regional initiatives introduced in the North Lancashire Teaching Primary Care Trust (NLTPCT) since 2004 to enhance the quality and efficiency of prescribing proton pump inhibitors (PPIs), statins and ezetimibe. In addition, to suggest additional measures that could be introduced in NLTPCT to further enhance the quality and efficiency of prescribing based on initiatives in other European countries.Method: A before-and-after observational study was undertaken on the utilization and expenditure of prescriptions dispensed in ambulatory care in NLTPCT from 2004 to 2007. Utilization was assessed using ''defined daily doses'' (DDDs) and ''DDDs/1000 inhabitants per day'' and compared over the study period. Reimbursed expenditure was assessed in terms of overall expenditure, expenditure/DDD, as well as expenditure/1000 inhabitants per year.Results: The combination of measures and initiatives enhanced the utilization of generic PPIs. International Nonproprietary Name (INN) prescribing of omeprazole reached 98% of all omeprazole by 2007. The measures also resulted in limited utilization of esomeprazole and lowered reimbursed expenditure/DDD of generic omeprazole to GB££0.13 by 2007. This was 87% below 2004 originator prices, leading to a 41% fall in PPI expenditure during the study period despite increased utilization. Utilization of statins grew by over 130% during the study period enhanced by increased utilization of high doses of simvastatin and atorvastatin following the introduction of the quality and outcomes framework. Simvastatin dominated statin utilization by 2007, with generic simvastatin accounting for over 99.5% of total simvastatin. Reimbursed expenditure/DDD for generic simvastatin was ££0.03 in 2007, 95% below 2004 originator prices, leading to a fall in overall expenditure on statins. It proved difficult to undertake an impact analysis as, typically, a range of measures were introduced sequentially and simultaneously during the study period.Conclusion: The findings are in line with expectations and do provide examples to other European countries. This includes a high rate of INN prescribing, low reimbursed prices for generic simvastatin and omeprazole and growing utilization of higher strength statins. The high rate of INN prescribing reduces the need for additional measures that have been instigated in other European countries to further enhance the prescribing and dispensing of generics to fully realize the resource benefits. Additional demand side measures are feasible and have already been instigated to conserve resources.